Effect of Electrostatic Interaction on Electrodeposition of Nickel Hexacyanoferrate with Functional MWCNTs and Their Application for the Determination of Persulfate and Tannic Acid - Tsai, Tsung-Hsuan; Yeh, Pin-Chun; Chen, Shen-Ming; Ali, M. Ajmal; Al-Hemaid, Fahad M. A. (Electroanalysis (New York, N.Y.), 2014)
A nanocomposite film of NiHCF electrodeposited onto AFCNT was modified on GCE by the electrostatic interaction of multiple scan cyclic voltammetry. Amino groups have been introduced with a positive charge onto the surface of MWCNTs. The presence of NiHCF‐AFCNT/GCE was characterized by using FE‐SEM, EDS, EIS, and XRD studies. The nanocomposite film of NiHCF‐AFCNT was further utilized to determine persulfate and tannic acid, respectively. The nanocomposite film modified electrode displays linear response from 0.1 to 19 mM and 10 to 170 µM for persulfate and tannic acid with a correlation coefficient of 0.9921 and 0.9869. The detection limits were found to be 0.1 mM and 1 µM, respectively. As results, the electrostatic interaction between positively charged metal ions, amino functionalized CNT and negatively charged hexacyanoferrate can be a new subject for many interesting applications.